Metode dan Pendekatan dalam Kajian Islam - Suparlan Suparlan (FONDATIA, 2019)
Islamic studies is one of the studies that has received attention among scientists. If explored in depth, it appears that Islamic studies began to be widely studied by those interested in religious studies and other studies. Thus, Islamic studies deserve to be used as one of the favorite branches of science. That is, the study of Islam has gained a place in the world of science. Approach is a perspective or paradigm used by a reviewer in analyzing an object of Islamic religion by using certain sciences or theories. Certain sciences or theories are basically used as a tool or analysis tool for problems related to religion so that the object and the environment of study are clearly visible.